Brazilian consensus recommendations on the diagnosis and treatment of autoimmune encephalitis in the adult and pediatric populations - Dutra, Lívia Almeida; Silva, Pedro Victor de Castro; Ferreira, João Henrique Fregadolli; Marques, Alexandre Coelho; Toso, Fabio Fieni; Vasconcelos, Claudia Cristina Ferreira; Brum, Doralina Guimarães; Pereira, Samira Luisa dos Apóstolos; Adoni, Tarso; Rocha, Leticia Januzi de Almeida; Sampaio, Leticia Pereira de Brito; Sousa, Nise Alessandra de Carvalho; Paolilo, Renata Barbosa; Pizzol, Angélica Dal; Costa, Bruna Klein da; Disserol, Caio César Diniz; Pupe, Camila; Valle, Daniel Almeida do; Diniz, Denise Sisterolli; Abrantes, Fabiano Ferreira de; Schmidt, Felipe da Rocha; Cendes, Fernando; Oliveira, Francisco Tomaz Meneses de; Martins, Gabriela Joca; Silva, Guilherme Diogo; Lin, Katia; Pinto, Lécio Figueira; Santos, Mara Lúcia Schimtz Ferreira; Gonçalves, Marcus Vinícius Magno; Krueger, Mariana Braatz; Haziot, Michel Elyas Jung; Barsottini, Orlando Graziani Povoas; Nascimento, Osvaldo José Moreira do; Nóbrega, Paulo Ribeiro; Proveti, Priscilla Mara; Castilhos, Raphael Machado do; Daccach, Vanessa; Glehn, Felipe von (Arquivos de Neuro-Psiquiatria, 2024)
Background Autoimmune encephalitis (AIE) is a group of inflammatory diseases characterized by the presence of antibodies against neuronal and glial antigens, leading to subacute psychiatric symptoms, memory complaints, and movement disorders. The patients are predominantly young, and delays in treatment are associated with worse prognosis.Objective With the support of the Brazilian Academy of Neurology (Academia Brasileira de Neurologia, ABN) and the Brazilian Society of Child Neurology (Sociedade Brasileira de Neurologia Infantil, SBNI), a consensus on the diagnosis and treatment of AIE in Brazil was developed using the Delphi method.Methods A total of 25 panelists, including adult and child neurologists, participated in the study.Results The panelists agreed that patients fulfilling criteria for possible AIE should be screened for antineuronal antibodies in the serum and cerebrospinal fluid (CSF) using the tissue-based assay (TBA) and cell-based assay (CBA) techniques. Children should also be screened for anti-myelin oligodendrocyte glucoprotein antibodies (anti-MOG). Treatment should be started within the first 4 weeks of symptoms. The first-line option is methylprednisolone plus intravenous immunoglobulin (IVIG) or plasmapheresis, the second-line includes rituximab and/or cyclophosphamide, while third-line treatment options are bortezomib and tocilizumab. Most seizures in AIE are symptomatic, and antiseizure medications may be weaned after the acute stage. In anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis, the panelists have agreed that oral immunosuppressant agents should not be used. Patients should be evaluated at the acute and postacute stages using functional and cognitive scales, such as the Mini-Mental State Examination (MMSE), the Montreal Cognitive Assessment (MoCA), the Modified Rankin Scale (mRS), and the Clinical Assessment Scale in Autoimmune Encephalitis (CASE).Conclusion The present study provides tangible evidence for the effective management of AIE patients within the Brazilian healthcare system.
Keywords: Autoimmune Encephalitis; Anti-N-Methyl-D-Aspartate Receptor Encephalitis; Delphi Technique; Rituximab; Tocilizumab